ANALISIS KINERJA PENGURUS PADA LEMBAGA MAJELIS ULAMA INDONESIA KABUPATEN BOGOR - Tohir, M. Abdullah; Rahmawati, Rita; Iskandar, Abubakar (Administratie: Jurnal Administrasi Publik, 2022)
Non-profit organizations such as MUI sometimes encounter suboptimal performance among their members. Therefore, this research aims to analyze the performance of the management within the Indonesian Council of Ulama (Majelis Ulama Indonesia) in Bogor Regency. The utilized method is descriptive analysis, involving the entire population of MUI management in Bogor Regency, totalling 198 individuals. The sample size was determined using Yamane's formula, resulting in a sample of 69 Ulama. Data were collected through questionnaires, interviews, observations, and literature review. The data were then analyzed using the Weight Mean Score (WMS) method. The research findings reveal that the average cumulative score for performance dimensions, assessed on a 1-5 interval scale, within MUI Bogor Regency is 4.78, interpreted as Very Good. The highest mean score is attributed to the Quality dimension with a score of 4.91, whereas the lowest mean score belongs to the Initiative dimension with a score of 4.64. The challenges faced in the performance of MUI Bogor Regency are related to the suboptimal initiation from MUI members. Efforts to enhance performance include the development of Human Resources through intensified cadre training and increased incentives for activities within MUI Bogor Regency.